Review of hydrodynamic instability experiments in inertially confined fusion implosions on National Ignition Facility. (24th October 2019) - Smalyuk, V A; Weber, C R; Landen, O L; Ali, S; Bachmann, B; Celliers, P M; Dewald, E L; Fernandez, A; Hammel, B A; Hall, G; MacPhee, A G; Pickworth, L; et al.
Abstract: Hydrodynamic instabilities are a major factor in degradation of inertial confinement fusion (ICF) implosions. In the highest performing implosions on National Ignition Facility, yield amplification (YA) due to alpha particle heating approached ∼3, while YA of ∼15–30 is needed for ignition. Understanding and mitigation of the instabilities are critical to achieving ignition. This article reviews several experimental platforms that have been developed to directly measure these instabilities in all phases of ICF implosions. Measurements of ripple-shock propagation at OMEGA laser has provided results on initial seeds for the instabilities in three ablators—plastic (CH), beryllium, and high-density carbon. At the ablation front, instability growth of pre-imposed modulations was measured in the linear regime using the hydrodynamic growth radiography platform. This platform was extended for modulation growth of 'native roughness' modulations and engineering features (fill tubes and capsule support membranes or 'tents'). Several new experimental platforms have or are being developed to measure instability growth at the ablator–ice interface. In the deceleration phase of implosions, complementary 'self-emission' and 'self-backlighting' platforms were developed to measure low-mode asymmetries and high-mode perturbations near peak compression.